Soil inorganic carbon storage pattern in China - Mi, Na (2008)
Soils with pedogenic carbonate cover about 30% (3.44 × 106 km2) of China, mainly across its arid and semiarid regions in the Northwest. Based on the second national soil survey (1979–1992), total soil inorganic carbon (SIC) storage in China was estimated to be 53.3±6.3 PgC (1 Pg=1015 g) to the depth investigated to 2 m. Soil inorganic carbon storages were 4.6, 10.6, 11.1, and 20.8 Pg for the depth ranges of 0–0.1, 0.1–0.3, 0.3–0.5, and 0.5–1 m, respectively. Stocks for 0.1, 0.3, 0.5, and 1 m of depth accounted for 8.7%, 28.7%, 49.6%, and 88.9% of total SIC, respectively. In contrast with soil organic carbon (SOC) storage, which is highest under 500–800 mm yr−1 of mean precipitation, SIC storage peaks where mean precipitation is <400 mm yr−1. The amount and vertical distribution of SIC was related to climate and land cover type. Content of SIC in each incremental horizon was positively related with mean annual temperature and negatively related with mean annual precipitation, with the magnitude of SIC content across land cover types showing the following order: desert, grassland >shrubland, cropland >marsh, forest, meadow. Densities of SIC increased generally with depth in all ecosystem types with the exception of deserts and marshes where it peaked in intermediate layers (0.1–0.3 m for first and 0.3–0.5 m for latter). Being an abundant component of soil carbon stocks in China, SIC dynamics and the process involved in its accumulation or loss from soils require a better understanding.